ARTIFICIAL INTELLIGENCE IN NIGERIAN PHYSIOTHERAPY: EXPLORING IMPLEMENTATION CHALLENGES AND OPPORTUNITIES (Journal of Biomedical Investigation, 2025)
Background: Artificial intelligence (AI) has emerged as a transformative tool in healthcare, with growing relevance in physiotherapy for improving assessment, diagnosis, and treatment planning. However, the integration of AI into clinical practice, particularly in low-resource settings such as Anambra State, Nigeria, faces numerous challenges.Aim: To identify the facilitators and barriers of AI applications in physiotherapy practices in Anambra state.Materials and methods: This study was a cross-sectional which used a convenience sampling technique to recruit 60 physiotherapists residing and/or working in Anambra State’s health facilities. Data were collected using a self-structured questionnaire and analysed using descriptive statistics.Results: Most participants (53.3%) were female, within the age group of 30–39 years. Most participants (88.0%) indicated that they had never used AI during treatment. Approximately 53.3% identified social media as the platform where they sourced information about the application of AI in physiotherapy, and 98.3% indicated that the application of AI cannot replace physiotherapists. Wearable devices were identified as the most impactful AI tool. The inability of AI to manage all patients’ health conditions or impairments, cost of AI equipment and treatment, and acceptance and adoption of AI technologies were identified as the major barriers.Conclusions: The findings indicated limited application of AI among physiotherapists, despite the potential for improvement through various supportive measures. Factors such as funding availability, training programs, and access to AI-powered platforms can significantly enhance the integration of AI in healthcare practices.
Keywords: Facilitators; Barriers; Artificial Intelligence; Physiotherapy; Healthcare Technology